Effect of low molarity alkaline solution on the compressive strength of fly ash based geopolymer concrete - Tan, Shea Qin; Nor Hasanah, Abdul Shukor Lim; Teng, Zhang Jun; Nur Farhayu, Ariffin (Sustainable Building Research Center (ERC) Innovative Durable Building and Infrastructure Research Center, 2022)
The escalating of cement production had significant effect on greenhouse gases emission, thus innovation of geopolymer concrete is crucial to reduce the environmental impacts. Besides, high concentration of alkaline solution not only exhibits corrosive nature, but also increases the cost of construction. Therefore, this research studies the engineering properties and effect of elevated temperature on fly ash-based geopolymer concrete using low molarity alkaline solution. The alkaline solution used in this research is sodium hydroxide (NaOH) combines with sodium silicate (Na2SiO3) with different molarity of 2M, 4M and 10M. The binder to solution ratio of 0.45, NaOH mixed with Na2SiO3 at mass ratio of 2.5 and binder to aggregates with proportion of 1:3 was fixed. Test specimens was prepared and tested at the age of 3, 7 and 28 days. Results show that with reduced alkaline solution molarity, the compressive strength reduced by 45 and 55% for geopolymer with 4M and 2M, respectively. However, the compressive strength exhibits are within the normal strength geopolymer concrete with comparable density and workability. Therefore, it can be concluded that low molarity geopolymer concrete can be applied in construction due to more environmentally friendly and lower cost.